Activity of Lymphostatin, A Lymphocyte Inhibitory Virulence Factor of Pathogenic Escherichia coli, is Dependent on a Cysteine Protease Motif. Issue 19 (17th September 2021) - Bease, Andrew G.; Blackburn, Elizabeth A.; Chintoan-Uta, Cosmin; Webb, Shaun; Cassady-Cain, Robin L.; Stevens, Mark P.
Graphical abstract: Highlights: LifA shares a cysteine protease motif with bacterial toxins and secreted effectors. C1480A substituted LifA has reduced inhibitory activity against T cells. LifA is cleaved in T cells and this requires C1480 and endosome acidification. Abstract: Lymphostatin (LifA) is a 366 kDa protein expressed by attaching & effacing Escherichia coli . It plays an important role in intestinal colonisation and inhibits the mitogen- and antigen-stimulated proliferation of lymphocytes and the synthesis of proinflammatory cytokines. LifA exhibits N-terminal homology with the glycosyltransferase domain of large clostridial toxins (LCTs). A DTD motif within this region is required for lymphostatin activity and binding of the sugar donor uridine diphosphate N -acetylglucosamine. As with LCTs, LifA also contains a cysteine protease motif (C1480, H1581, D1596) that is widely conserved within the YopT-like superfamily of cysteine proteases. By analogy with LCTs, we hypothesised that the CHD motif may be required for intracellular processing of the protein to release the catalytic N-terminal domain after uptake and low pH-stimulated membrane insertion of LifA within endosomes. Here, we created and validated a C1480A substitution mutant in LifA from enteropathogenic E. coli strain E2348/69. The purified protein was structurally near-identical to the wild-type protein. In bovine T lymphocytes treated with wild-type LifA, a putative cleavage product of approximately 140 kDa was detected. Appearance of the putative cleavage product was inhibited in a concentration-dependent manner by bafilomycin A1 and chloroquine, which inhibit endosome acidification. The cleavage product was not observed in cells treated with the C1480A mutant of LifA. Lymphocyte inhibitory activity of the purified C1480A protein was significantly impaired. The data indicate that an intact cysteine protease motif is required for cleavage of lymphostatin and its activity against T cells.